Psychological Emotion Recognition of Students Based Chatbot - Senapati, Atharva; Anuja Phapale (MultiTech Publisher, 2023)
In the context of modern education, where students' emotional well-being plays a crucial role in academic success, the integration of technology, particularly machine learning-based chatbots, presents a promising avenue to support and recognize the psychological states of students. This paper delves into the development and evaluation of a chatbot system designed to recognize and respond to the emotions expressed by students. Leveraging natural language processing and sentiment analysis, the chatbot engages in conversations with students, allowing for the real-time recognition of emotional states. Our study does not only focus on the technical aspects of emotion recognition but also exploration the implications and ethical considerations of deploying such technology in educational settings. By shedding light on the potential of machine learning-based chatbots to enhance emotional support and understanding within educational environments, this research contributes to the ongoing dialogue on students well-being and the role of technology in education.